Шунды эш утча: нылпиослы кылбуръёс / Лия Малых ; [художник Т. И. Немцева] - Малых Лия Яковлевна (Удмуртия, 2021)
Экземпляры: ф.2 (2022) / Инвентарный номер: 57961 / Цена: / Сис.шифр: К84(2Рос=Удм) / Авт.знак: М 20 / ГРНТИ: 17.82 / ББК: 84(2=664.1)-5